Review of Fault Detection and Diagnosis Methods Including Failure Root Causes of Major Components of Hydraulic Pitch System for Wind Turbines-Part-I - Wrat, Gyan; Bhola, Mohit; Chamorro, Diego M.; Liniger, Jesper; Pedersen, Henrik C. (International Journal of Fluid Power, 2025)
The hydraulic pitch system is one of the critical sub-systems of the wind turbine for both power regulation and also as part of the safety system by applying aerodynamic braking during the duration of extreme weather events. Various studies of wind turbine reliability have revealed that the hydraulic pitch system is one of the major contributors to the turbine’s downtime. Therefore, the focus of this study deals with the identification and mapping of failures in hydraulic pitch systems and the main components based on state-of-the-art failure mode knowledge and detection methods found in the literature. In this work, Fault Tree Analysis (FTA) is utilized to evaluate failures all the way down to root causes of major hydraulic components, i.e., on-off solenoid valves, proportional valves, hydraulic cylinders, and sensors used in hydraulic pitch systems. This facilitates a comprehensive understanding of failure modes and root causes within these hydraulic components. Nevertheless, the focus of this study has hence been to identify the methods to enhance fault detection and predictive maintenance strategies, ultimately improving the reliability and efficiency of hydraulic systems across various applications.